Waste-to-methanol: Direct CO2 Emissions Assessment for the Methanol Production from Municipal Waste-derived Syngas - Enrico Catizzone; Aristide Giuliano; Diego Barletta (Chemical Engineering Transactions, 2021)
The valorization of municipal waste represents one of the major opportunities for the next future. In particular, the Organic Fraction of Municipal Solid Waste (OFMSW) can be used in anaerobic digesters to produce biogas/biomethane. Furthermore, a fraction of Municipal Solid Waste (e.g. non-recyclable plastics, paper cardboard, etc.) can be converted to Refuse Derived Fuel (RDF). Both biogas/biomethane and RDF may be further converted in syngas (a mixture of H2, CO and CO2) by using several technologies, such as steam reforming for the former, and gasification for the latter. Syngas may be used as fuel in CHP plants or for the production of chemical intermediates and fuel. The digestate derived from anaerobic digestion, as well as CO2 from biogas, can be used as nutrients source to grow microalgae, which are feedstock suitable for supercritical water gasification (SWG). In this paper, an integrated process is proposed, by coupling an anaerobic digestion plant for biomethane production with (i) high-temperature gasification of RDF and (ii) SWG of algae grown up with digestate and CO2 from biogas. The biomethane is assumed to be converted in syngas by steam reforming. Considering its importance for the chemical industry chain, methanol is considered as a target product. Methanol synthesis is assessed in terms of mass and energy balances and direct CO2 emissions. The results show that high-temperature endothermic processes require the use of purge gas as a fuel in a burner to sustain itself. The lowest direct CO2 emission value per kg of methanol produced is obtained in the case of high use of RDF, minimum recycling of CO2 to algae production and minimum purge ratio.